Study of Impact Dynamic Characteristics and Damage Morphology of Layered Rock Mass. (25th October 2022) - Tian, Xingchao; Tao, Tiejun; Xie, Caijin
Abstract : To explore the dynamic mechanical properties and damage evolution law of the more common layered rock masses in geotechnical engineering, this paper determined the Holmquist–Johnson–Cook (HJC) constitutive model parameters of dolomite, gray sandstone, and limestone according to the static mechanical parameters of the rock mass. We used Hypermesh/ANSYS software to establish the numerical analysis model, carried out the dynamic impact numerical simulation of the layered rock mass, and analyzed the stress wave propagation characteristics, dynamic stress–strain relationship, energy dissipation, and damage evolution laws of layered rock masses under different combinations. At the same time, this paper analyzed the stress characteristics of the layered rock mass and studied its failure characteristics. The research results show that the wave impedance matching relationship alters the dynamic characteristics of the layered rock mass; however, with the increase in impact velocity, the difference gradually weakens. The difference in elastic modulus leads to different initial failure modes of layered rock masses, and the quality of the wave impedance matching relationship leads to differences in the law of damage evolution of layered rock masses. Under different combination forms, the failure degree and failure modes of the two parts of the layered rock mass are different.